Analysis of Indonesian Coffee Production, Area, and Consumption Trends in 2022-2026: Opportunities and Challenges in Maintaining the Sustainability of the National Coffee Sector - Zargustin, Dedi; Harmaidi, Desma; Nurwati, Niken; Susi, Neng (International Journal Labs, 2025)
This study analyzes the projections of coffee production, area, and consumption in Indonesia in the period 2022–2026 to identify opportunities and challenges in the sustainability of the national coffee sector. A descriptive qualitative approach is employed, using secondary data processed through multiple regression methods and ARIMA models for trend estimation. Secondary data were processed using multiple regression methods and ARIMA models for trend estimation. The results of the analysis show that coffee production tends to be stagnant with an average of 790,103 tons per year, experiencing an average annual decline of 0.12%. Meanwhile, the coffee area shows an average positive growth trend of 0.66% per year, reaching 1,296,254 hectares in 2026. Domestic consumption decreased by an average of 1.19% per year, from 379,655 tons in 2022 to 361,837 tons in 2026. Net coffee exports actually increased consistently by an average of 0.83% per year. This study concludes the need to increase productivity and diversify the domestic market to maintain the sustainability of the coffee sector, amid increasing exports and changing consumption trends. The need for strategies to address declining domestic consumption and stagnating production trends, despite positive growth in coffee cultivation areas and net exports. It emphasizes recommendations such as adopting sustainable farming practices, increasing productivity through technological innovation, and diversifying coffee products to cater to both domestic and international markets. Additionally, it suggests strengthening Indonesia’s competitiveness in the global coffee market by investing in branding, marketing, and value-added products.